Rancang Bangun Sistem Informasi Pelayanan pada Pusat Kesehatan Masyarakat - Ahmad Sahal; Zaidir Zaidir; Farida Nur Aini (Progresif: Jurnal Ilmiah Komputer, 2023)
Optimal service is the main goal of the Community Health Center as a center for public health services. Utilizing reliable information technology to improve services is urgently needed. The problem at the City Health Center in Manggarai Regency, East Nusa Tenggara is that the presentation of data in each polyclinic is still not integrated and systematic, starting from registration, especially giving medical record numbers, patient care, and administering drugs, so it still needs to be improved. This paper presents an Information System model for services at Puskesmas, which was developed using the Waterfall method. The developer software used is VB.Net and PostgreSQL, which are tested using the Black Box testing method. The resulting puskesmas service information system can be used for services ranging from patient registration, services to polyclinics to drug services that can be carried out, so that it can facilitate services while at the same time presenting the necessary reports and improving the performance of the puskesmas.Keywords: Design and Build; Information Systems; Community Health Center Services; Medical Records AbstrakPelayanan yang optimal adalah tujuan utama Puskesmas yang menjadi pusat pelayanan kesehatan masyarakat. Memanfaatkan teknologi informasi yang handal untuk peningkatan pelayanan sangat dibutuhkan. Permasalahan di Puskesmas Kota Kabupaten Manggarai Nusa Tenggara Timur adalah penyajian data di setiap poliklinik masih belum terintegrasi dan sistematis, mulai dari pendaftaran terutama pemberian nomor rekam medis, perawatan pasien, dan pemberian obat, sehingga masih perlu di tingkatkan. Paper ini menyajikan model Sistem Informasi untuk pelayanan pada Puskesmas, yang dikembangkan menggunakan metode Waterfall. Perangkat lunak pengembang yang pakai adalah VB.Net dan PostgreSQL, yang diuji menggunakan metode pengujian Black Box testing. Sistem informasi pelayanan puskesmas yang dihasilkan, dapat digunakan untuk pelayanan mulai dari pendaftaran pasien, pelayanan ke poli sampai pelayanan obat dapat dilakukan, sehingga dapat mempermudah pelayanan sekaligus dapat menyajikan laporan yang diperlukan serta meningkatkan kinerja Puskesmas.Kata Kunci: Rancang Bangun; Sistem Informasi; Layanan Puskesmas; Rekam Medis